Determinants of Rice Productivity: An Analysis of Jaffarabad District –Balochistan (Pakistan) - Sarfaraz Ahmed Shaikh; Ouyang Hongbing; Khalid Khan; Masood Ahmed (European Scientific Journal, ESJ, 2016)
This study examines the determinants of rice production in the district of Jaffarabad in Balochistan using primary data. The data is collected with the help of well-developed questionnaire based on random sampling from the different tehsils of Jaffarabad district. In this study, we estimated the parameters of the Neo-classical and Cobb-Douglas production function with the help of ordinary least square (OLS) method. The results of this empirical work show that with the exception of experience of farmers and high cost of the inputs, all explanatory variables i.e. capital, labor, education of the farmers, availability of credit and farm size have a positive effect on rice output. Therefore, government is recommended to encourage farmers to use fertilizers and new methods in agricultural production and watering, and provide them with convenient loans at low interest rate.